A single center 10‐year clinical experience with superior vena cava retrievable filters. Issue 1 (14th October 2019) - Lopera, Jorge E.; Barnes, Laura
Abstract: Purpose: To report a 10‐year clinical experience with superior vena cava (SVC) retrievable filters. Methods: A retrospective review of patients with SVC filters was performed between 2008 and 2018 in a single tertiary medical center. Patient demographics, indications for filter placement, type of filter placed, and clinical evolution were recorded. Complications during placement, retrieval, and follow‐up were determined. Results: Fifty patients ages 17–89 years (average 54) underwent SVC retrievable filter placement. Main indication for filter placement was deep venous thrombosis of the major upper extremity and/or internal jugular veins with contraindications to anticoagulation. Complications during placement included inadvertent filter placement in the right brachiocephalic vein in two patients, another patient had a leg of the filter entrapped in the tip of a hemodialysis catheter that required filter reposition and line exchange. Thirteen patients had attempted retrieval with 12 filters successfully removed 7–420 days after placement (mean 170). On follow‐up images available in 24 patients, 13 filters were noted to be significantly tilted and 10 filters had evidence of leg penetration. No other serious late complications were noted. Conclusion: The use of retrievable SVC filters in patients with upper extremity DVT is highly questionable. There is a high incidence of filter malposition, filter tilting, and leg penetration.